Commencement 2004 (Institutional Knowledge at Singapore Management University, 2004)
Deputy Prime Minister Dr Tony Tan addressing students at Singapore Management University's inaugural commencement ceremony held on 10 July 2004. Three hundred and nine students from the pioneer class of undergraduates were awarded bachelor's degrees in business management or accountancy. Twenty-one students earned double bachelor's degrees. In addition, the ceremony also marked the graduation of forty-one students who earned master of science in applied finance degrees. The event was held at Raffles City Convention Centre.